2022
DOI: 10.3390/bios12070533
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Fluorescence Detection of Colorectal Cancer-Associated Exosomal miR-92a-3p with DSN-Assisted Signal Amplification by a MWCNTs@Au NCs Nanoplatform

Abstract: The detection of miRNA shows great promise in disease diagnosis. In this work, a ratiometric fluorescent biosensor based on multi-walled carbon nanotubes@gold nanoclusters (MWCNTs@Au NCs) and duplex-specific nuclease (DSN)-assisted signal amplification was fabricated for miRNA detection. Colorectal cancer (CRC)-associated miR-92a-3p extracted from exosomes was selected as the target. MWCNTs@Au NCs performs the dual functions of fluorescence quencher and internal fluorescence reference. In the absence of miR-92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The Measurements of various fluorescence emission spectra indicated that 12 minutes is the optimal duration for duplex formation (Figure 4C). MWCNTs@Au NCs, Atto-425 miR-92a-3p 0.1 -10 0.031 (43) In this study miRNA-21 -1.12 relationship between fluorescence intensity and cDNA concentration was nonlinear, described by the equation y = -1.2031x + 11.986 with an R 2 value of 0.7594. By examining the fluorescence response of the biosensor to cDNA and a mismatched DNA, a qualitative analysis was conducted to assess the selectivity of the miRNA sensing platform.…”
Section: Design Strategymentioning
confidence: 67%
“…The Measurements of various fluorescence emission spectra indicated that 12 minutes is the optimal duration for duplex formation (Figure 4C). MWCNTs@Au NCs, Atto-425 miR-92a-3p 0.1 -10 0.031 (43) In this study miRNA-21 -1.12 relationship between fluorescence intensity and cDNA concentration was nonlinear, described by the equation y = -1.2031x + 11.986 with an R 2 value of 0.7594. By examining the fluorescence response of the biosensor to cDNA and a mismatched DNA, a qualitative analysis was conducted to assess the selectivity of the miRNA sensing platform.…”
Section: Design Strategymentioning
confidence: 67%
“…EV‐miRNAs are associated with the progression of many cancers, and several emerging assays have been validated in clinical samples, mostly from serum or plasma, but also from urine and some tissue fluids. These assays detect single or multiple miRNAs for the diagnosis of related diseases such as PDAC, [ 98 ] breast cancer, [ 99 ] CRC, [ 100 ] thyroid cancer, [ 101 ] and oral squamous cell carcinoma. [ 102 ] Emerging assays have shown good performance in the detection of EV‐miRNAs due to their high specificity and sensitivity ( Table 2 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…For example, Yang et al achieved the imaging of the CAC and PSP points of the sodium carboxymethyl cellulose-stepanol WA-100 system [ 18 ]. Among these techniques, the fluorimetry-based ones have attracted wide interest because of their high sensitivity and low background [ 19 , 20 ]. For instance, Jiao et al reported a fluorescence imaging tool that illustrates the CAC and PSP points of chitosan and tetraphenylethene-modified sodium dodecyl sulfonate surfactant (TPE-SDS) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%